Global account management: what it is and what it isn’t - Yip, George S. (Henry Stewart Talks, 2014)
Strategic account management, Key account management, Global account management, Global marketing, Global strategy – Organization, Global customers, Customer relationship management
Reviewed at 2020/06/30